2011
DOI: 10.1111/j.1468-8123.2011.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfosalt melts and heavy metal (As‐Sb‐Bi‐Sn‐Pb‐Tl) fractionation during volcanic gas expansion: the El Indio (Chile) paleo‐fumarole

Abstract: 2012). Sulfosalt melts and heavy metal (As-Sb-Bi-Sn-Pb-Tl) fractionation during volcanic gas expansion: The El Indio (Chile) paleo-fumarole. Geofluids, 12 (3),[199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214][215] Sulfosalt melts and heavy metal (As-Sb-Bi-Sn-Pb-Tl) fractionation during volcanic gas expansion: The El Indio (Chile) paleo-fumarole AbstractHigh-sulfidation vein gold deposits such as El Indio, Chile, formed in fracture arrays <1000m beneath paleosolfatara in volcanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 44 publications
(96 reference statements)
0
30
0
Order By: Relevance
“…2): (1) pre-ore massive pyrite vein filling ('early pyrite'); (2) enargitetennantite mineralization (containing up to 10 % Cu and 120 ppm Ag), followed by; and (3) 'Au-stage' (>100 ppm Au) quartz-pyrite-sulfosalt veins (containing 'late pyrite') (Jannas et al 1990;Deyell et al 2004). Jannas et al (1990Jannas et al ( , 1999 observed that massive enargite and pyrite fill 'Cu-stage' veins; however, Henley et al (2012) clarify that deposition of massive pyrite veins preceded sulfosalt mineralization at El Indio, as veins of sulfosalt fill fractures crosscutting massive pyrite. Hence, we refer to this massive pyrite as 'early pyrite,' Sulfosalt phase relations and trace element chemistry suggest that sulfosalt assemblages condensed from one-phase magmatic vapor 1 above 665 °C and below 694 °C (the melting point of the crystalline enargite that precedes Fe-tennantite) (Henley et al 2012).…”
Section: Geology Of the El Indio Au-ag-cu High-sulfidation Depositmentioning
confidence: 99%
See 3 more Smart Citations
“…2): (1) pre-ore massive pyrite vein filling ('early pyrite'); (2) enargitetennantite mineralization (containing up to 10 % Cu and 120 ppm Ag), followed by; and (3) 'Au-stage' (>100 ppm Au) quartz-pyrite-sulfosalt veins (containing 'late pyrite') (Jannas et al 1990;Deyell et al 2004). Jannas et al (1990Jannas et al ( , 1999 observed that massive enargite and pyrite fill 'Cu-stage' veins; however, Henley et al (2012) clarify that deposition of massive pyrite veins preceded sulfosalt mineralization at El Indio, as veins of sulfosalt fill fractures crosscutting massive pyrite. Hence, we refer to this massive pyrite as 'early pyrite,' Sulfosalt phase relations and trace element chemistry suggest that sulfosalt assemblages condensed from one-phase magmatic vapor 1 above 665 °C and below 694 °C (the melting point of the crystalline enargite that precedes Fe-tennantite) (Henley et al 2012).…”
Section: Geology Of the El Indio Au-ag-cu High-sulfidation Depositmentioning
confidence: 99%
“…Jannas et al (1990Jannas et al ( , 1999 observed that massive enargite and pyrite fill 'Cu-stage' veins; however, Henley et al (2012) clarify that deposition of massive pyrite veins preceded sulfosalt mineralization at El Indio, as veins of sulfosalt fill fractures crosscutting massive pyrite. Hence, we refer to this massive pyrite as 'early pyrite,' Sulfosalt phase relations and trace element chemistry suggest that sulfosalt assemblages condensed from one-phase magmatic vapor 1 above 665 °C and below 694 °C (the melting point of the crystalline enargite that precedes Fe-tennantite) (Henley et al 2012). Since the stability limit of pyrite is 742 °C and no major break in the paragenetic sequence is observed, it is reasonable to conclude that pyrite deposition occurred between 665 and 742 °C.…”
Section: Geology Of the El Indio Au-ag-cu High-sulfidation Depositmentioning
confidence: 99%
See 2 more Smart Citations
“…In principle, co-existing polymetallic melts in hydrothermal systems can partition metals from the fluid and concentrate them as melt components (Douglas, 2000), and sulfosalt melts have been shown to Ore Geology Reviews 99 (2018) 344-364 have condensed from expanding magmatic vapour at temperatures of ∼650°C in the El Indio paleo-fumarole (Henley et al, 2012;Henley and Berger, 2013;Mavrogenes et al, 2010). Semi-metals like Bi and Te at high concentrations can act as powerful fluxes, lowering the melting point of metals such as Au and the PGE -for example the Au-Bi melt has a eutectic at 241°C (Gather and Blachnik, 1974;Okamoto and Massalski, 1983).…”
Section: The Role Of Semi-metals In Pge Enrichmentmentioning
confidence: 99%